Environmental management system in accordance with the requirements of the international standard (ISO 14004) and its applicability "Case study at Al-Ma'mun plant (vegetable oil)" - محمد, رجاء جاسم (Journal of Economics and Administrative Sciences, 2009)
The search aims to clarify pollution to negative effects on environment and to an increasing in the dangerous polluted materials that discharged out these factories. To make active procedures in order to limit the environmental pollution.    The search problem came from an assumption which has the researched factory is suffering from the lack of applying the international specification      ( ISO 14004 ). The research problem assimilated by these questions:• What is the level or organization in thinking of environmental system according to ISO 14004 .• What are the requirements used in researched factory apply ISO 14004. To reach to the aim of search, the researcher depend on case study, in addition of using single basic hypothesis according to the used testing paper to  make or making the searched factory applied ecological system management according to ISO 14004.      The search reach to find partial application to the ecological management, and this will make suitable ecology to apply the system. And the search recommended applying ISO 14004 to reach to the ecological limit level.